2010
DOI: 10.1021/ie100011z
|View full text |Cite
|
Sign up to set email alerts
|

Immobilized Inulinase on Grafted Alginate Beads Prepared by the One-Step and the Two-Steps Methods

Abstract: Grafted alginate beads were prepared using the Encapsulator by two methods, the one-step and the two-step. The methods of grafting were characterized by thermal gravimetric analysis and infrared (IR). The glass transition (Tg) of both grafted gel beads showed gradual thermal improvement over the control gel. However, the one-step method showed higher Tg (231 °C) compared to the two-step method (220 °C). Both methods were also evaluated for immobilization of an important industrial enzyme, inulinase, to produce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
52
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(56 citation statements)
references
References 28 publications
2
52
0
Order By: Relevance
“…Figure 6 also demonstrates that the increase of the temperature had a negative effect in the improvement of enzyme adsorption, with loading capacity of 605 U.g -1 support and 264 U.g -1 support at 30 and 50 o C, respectively. For comparison purposes, Missau et al 16 found similar results regarding the inulinase immobilization on alginate-chitosan beads, achieving 668 U.g -1 gel beads at 50 o C. Grafted alginate beads showed an inulinase loading capacity of 530 U.g -1 gel beads 19 . Chitin 21 and silica 41 were used as inulinase supports, reaching 291 U.g -1 chitin and 43 U.g -1 silica, respectively.…”
Section: Resultsmentioning
confidence: 87%
See 1 more Smart Citation
“…Figure 6 also demonstrates that the increase of the temperature had a negative effect in the improvement of enzyme adsorption, with loading capacity of 605 U.g -1 support and 264 U.g -1 support at 30 and 50 o C, respectively. For comparison purposes, Missau et al 16 found similar results regarding the inulinase immobilization on alginate-chitosan beads, achieving 668 U.g -1 gel beads at 50 o C. Grafted alginate beads showed an inulinase loading capacity of 530 U.g -1 gel beads 19 . Chitin 21 and silica 41 were used as inulinase supports, reaching 291 U.g -1 chitin and 43 U.g -1 silica, respectively.…”
Section: Resultsmentioning
confidence: 87%
“…It may produce high fructose syrups by enzymatic hydrolysis, and are used for the production of fructooligosaccharides, which are functional food ingredients. Inulinase has been immobilized by adsorption on different supports such as grafted alginate beads 19 , aminated non-porous silica 20 and chitin 21 . However, the inulinase immobilization using the ZnWO 4 oxide as support has not been explored yet.…”
Section: Introductionmentioning
confidence: 99%
“…Immobilization of enzymes is one of the main methods used to stabilize free enzymes (Elnashar, 2010a;Danial et al, 2010). The support material and the main methods of immobilization are key parameters in enzyme immobilization.…”
Section: Methods Of Immobilizationmentioning
confidence: 99%
“…They were alternatively immobilized on solid supports (Fig. 1b) so that they can be easily separated from the products by simple filtration or using a fluidized magnetized bed reactor system (Danial et al, 2010, Elnashar, 2010aElnashar et al, 2008Elnashar et al, , 2009aElnashar et al, , 2009bYassin 2009a, 2009b;Mansour et al, 2007).…”
Section: Methods Of Immobilizationmentioning
confidence: 99%
“…In the immobilization process enzymes are trapped in a solid matrix, therefore, is possible the reuse and it will not be subjected to denaturation 25 . Several materials with different characteristics such as natural clay 26 , grafted alginate beads 27 , aminated non-porous silica nanoparticles 28 , chitin 29 , alginate-chitosan beads 30 , poly(EGDMA) cryogels 31 and carbon nanotubes 32 have been used as supports for inulinase immobilization by adsorption process. The immobilization process presents some advantages compared with free enzyme, which are the easily removed of the products from immobilized enzymes and possibility the continuous mode of operation 33 .…”
Section: Introductionmentioning
confidence: 99%